The Good and the Right as Evolutionary: Von Hayek’s Theory - Boland, D. (Journal of Income Distribution®, 1992)
The very basis we employ for determining the good and the right circumscribes the social structures and activities we consider legitimate. Three theories historically have dominated that determination. A fourth alternative, offered by Freidrich von Hayek, undergirds a system of limited government wherein much activity falls to a voluntary sector that takes on an importance akin to that of business and government. An appreciation of Von Hayek’s evolutionary social morality mitigates many objections to his policy recommendations, or at least shifts the foci of debates. To this end the theory is presented and contrasted with its contradiction, utilitarian, and ‘theocratic’ rivals.